Assessing Demand and Training for Welders in the Southeast Wisconsin Region - (:unkn) unknown (My University, 2008)
Under contract with the Waukesha-Ozaukee-Washington (WOW) Workforce Development, Inc., the Employment and Training Institute conducted a targeted survey of welder job openings and anticipated needs among fabricated metal product manufacturing firms and other large manufacturing employers in the seven-county region of Southeast Wisconsin. Data on welders from U.S. Census 2000 were examined for the seven counties to profile the demographics of existing welders, including those presently unemployed and those nearing retirement age. The four technical colleges in the Southeast Wisconsin region provided information on the locations, course offerings, and enrollment capacity for welding associate degree, diploma and certificate programs. Each of the technical colleges (Waukesha County, Moraine Park, Gateway, and Milwaukee Area) has increased or is anticipating enhanced welding offerings. A fourteen-page booklet was developed to provide information for high school students on careers in welding and contact information on local training programs.
Keywords: welding jobs; job training; technical college